Tubular polyoxoanion [(SeMo6O21)2(C2O4)3]10− and its transformations. (29th March 2021) - Pantyukhina, Valeria S.; Volchek, Victoria V.; Komarov, Vladislav Yu.; Korolkov, Ilya V.; Kokovkin, Vasily V.; Kompankov, Nikolay B.; Abramov, Pavel A.; Sokolov, Maxim N.
Abstract : Tubular [(SeMo6 O21 )2 (C2 O4 )3 ] 10− polyoxoanion can be assembled from Na2 MoO4 /SeO2 /H2 C2 O4 system. TBABr precipitates complexes of [Mo6 O19 ] 2− and [β-Mo8 O26 Na2 (NO3 )] 3− from its aqueous solution. Speciation of [β-Mo8 O26 ] 4− and [Mo6 O19 ] 2− has been studied. Abstract : Self-assembly reactions in the Na2 MoO4 /SeO2 /H2 C2 O4 system lead to the formation of a tubular [(SeMo6 O21 )2 (C2 O4 )3 ] 10− hybrid polyanion, isolated and characterized by single crystal X-ray diffraction (SCXRD) as Na9 H[(SeMo6 O21 )2 (C2 O4 )3 ]·NaNO3 ·20.6H2 O (SeMo6-1 ). Dehydration of this compound leads to the formation of Na10 [(SeMo6 O21 )2 (C2 O4 )3 ]·0.5NaNO3 ·8H2 O (SeMo6-2 ). The electrochemical behavior of SeMo6-2 as a component of the paste electrode was studied by CV in CH3 CN solution. A concentrated aqueous solution of SeMo6-2 was studied using 77 Se and 95 Mo NMR techniques, which show extensive degradation of the complex. Addition of TBABr to the concentrated solution leads to a precipitate consisting of TBA salts of [Mo6 O19 ] 2− and [β-Mo8 O26 Na2 (NO3 )2 ] 2− anions. The latter was characterized by SCXRD as (TBA)3 [β-Mo8 O26 Na2 (NO3 )]·CH3 CN (Mo8-Na ). This transformation shows the presence of [β-Mo8 O26 ] 4− and [Mo6 O19 ] 2− in the aqueous solution of SeMo6-2 . The study of (NBu4 )4 [β-Mo8 O26 ] and (NBu4 )2 [Mo6 O19 ] solutions in CH3 CN by HPLC shows equilibration between [β-Mo8 O26 ] 4− and [Mo6 O19 ] 2− .